Structure and function of the epidermal barrier in patients with atopic dermatitis – treatment options. Part one - Pelc, Jagoda; Czarnecka-Operacz, Magdalena; Adamski, Zygmunt (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Atopic dermatitis is a chronic, recurrent inflammatory skin disease, which is frequently familial. The main cause of the disease seems to be a defect of the epidermal barrier resulting from a genetic predisposition concerning the epidermis, functioning of the immune system as well as environmental factors (which are not related to the immune system). Genes responsible for encoding protein S100, filaggrin, proteases and their inhibitors are the main genes related to the problem of epidermal barrier dysfunction. There is a close connection between structural and immunological processes. Increased expression of cytokine Th2 profile belongs to the latter category. The objective of the present paper is to describe the influence of aforementioned factors on epidermis structure and dysfunction which leads to clinical symptoms of atopic dermatitis.